Legal Protection for Auction Winners of Mortgage Execution Objects: Perlindungan Hukum Terhadap Pemenang Lelang Atas Objek Eksekusi Hak Tanggungan - Azzahra, Salsabila Fathimah; Badriyah, Siti Malikhatun (Universitas Islam Indonesia, 2023)
Carrying out an auction is the payment of the auction object from the buyer to the auction seller, with the aim of paying off the debtor's debt to the creditor. However, in its implementation obstacles often arise such as the auction object cannot be controlled by the winning party. This research aims to determine legal protection for auction winners, as well as other obstacles faced by auction winners. In this research, the approach methods applied include: case approach methods through court decisions and statutory regulations. The legal materials used in this research use secondary legal materials in the form of primary legal materials, secondary legal materials and tertiary legal materials. The results of this research are legal protection for the rights of auction winners in the form of repressive protection contained in HIR, Vendu Regulation, PMK No. 213/PMK.06./2020, and the Civil Code. To obtain their rights, they can make real execution efforts. Meanwhile, in this research, the obstacles that influence the auction winner are non-juridical obstacles.Keywords: Execution; Mortgage right; Legal protection AbstrakPelaksanaan lelang merupakan pembayaran objek lelang dari pembeli kepada penjual lelang, dengan tujuan pelunasan hutang debitur kepada kreditur. Namun, dalam pelaksanaanya sering muncul hambatan seperti objek lelang tidak bisa dikuasai oleh pihak pemenang. Penelitian ini bertujuan untuk mengetahui perlindungan hukum terhadap pemenang lelang, serta hambatan lain yang dihadapi pemenang lelang. Penelitian ini menggunakan metode pendekatan pendekatan kasus melalui pendekatan putusan pengadilan dan pendekatan peraturan perundang-undangan. Bahan hukum yang digunakan adalah bahan hukum sekunder yang berupa bahan hukum primer, bahan hukum sekunder dan bahan hukum tersier. Hasil penelitian menyimpulkan bahwa perlindungan hukum terhadap hak pemenang lelang berupa perlindungan represif yang terdapat dalam HIR, Vendu Reglement, PMK No. 213/PMK.06./2020, dan KUHPerdata. Untuk mendapatkan haknya dapat melakukan upaya eksekusi riil. Hambatan yang berpengaruh pada pemenang lelang berupa hambatan non yuridis. Kata-kata kunci: Eksekusi; Hak Tanggungan; Perlindungan Hukum